Plug-and-display nanoparticle immunization of the core epitope domain induces potent neutralizing antibody and cellular immune responses against PEDV - Minghui Li; Yilan Chen; Siqiao Wang; Xueke Sun; Yongkun Du; Siyuan Liu; Ruiqi Li; Zejie Chang; Peiyang Ding; Gaiping Zhang (Journal of Integrative Agriculture)
Porcine epidemic diarrhea virus (PEDV), an enteric coronavirus, is widely spread worldwide and causes huge economic losses. The effective measure to control the viral infection is to develop ideal vaccines. Here, the collagenase equivalent domain (COE) of PEDV was displayed on the surface of nanoparticles (NPs) in order to develop a newer, safer and more effective subunit vaccine against PEDV. The monomeric COE was displayed on the mi3 protein, which self-assembles into nanoparticles composed of 60 subunits, using the SpyTag/SpyCatcher system. The size, zeta potential, microstructure of the COE-mi3 virus-like particles (VLPs) were investigated. The COE-mi3 VLPs that possessed good security, stability and better retention can be more efficiently taken up by antigen-presenting cells (APCs) and help promote dendritic cells (DCs) maturation. Moreover, COE-mi3 VLPs could prominently improve specific antibody levels including neutralizing antibodies (NAbs), and serum IgG, mucosal IgA. Moreover, COE-mi3 VLPs elicited more activation of CD4+ and CD8+ T cells and production of IFN-γ and IL-4 cytokines. In particular, COE-mi3 VLPs is an effectual antigen-delivery platform to enhance germinal center (GC) B cell responses. This structure-based self-assembly of NP gives great potential to be developed as a new subunit vaccines attractive platform, and may also provide new ideas for the development of other enteric coronavirus vaccines.